The impact of uncertainty shocks under measurement error: A proxy SVAR approach - Andrea Carriero; Haroon Mumtaz; Konstantinos Theodoridis; Angeliki Theophilopoulou (Queen Mary University of London, School of Economics and Finance, 2013)
A growing empirical literature has considered the impact of uncertainty using SVAR models that include proxies for uncertainty shocks as endogenous variables. In this paper we consider the possible impact of measurement error in the uncertainty shock proxies on the estimated impulse responses from these SVAR models. We show via a Monte Carlo experiment that measurement error can result in attenuation bias in the SVAR impulse responses. In contrast, the proxy SVAR that uses the uncertainty shock proxy as an instrument to identify the underlying shock does not suffer from this bias. Applying this proxy SVAR method to the Bloom (2009) data set results in estimated impulse responses to uncertainty shocks that are larger in magnitude and persistence than those obtained from a standard recursive SVAR.
Keywords: C15; C32; E32; 330; Uncertainty shocks; Proxy SVAR; Non-linear DSGE models